ENGINE PROPELLER MATCHING ANALYSIS ON FISHING VESSEL USING INBOARD ENGINE - Santosa, Ari Wibawa Budi; Mausulunnaji, Muhammad Fathan; Setiyobudi, Nanang; Chrismianto, Deddy; Hadi, Eko Sasmito (Journal of Applied Engineering Science, 2022)
Fishing vessels which are used for one day operations usually use outboard engines as their driving motor. However, to improve the performance of propulsion systems, and consequently the performance of ships, inboard engines are now being used. In this study, the propulsion system of a ship was modified by upgrading from an outboard to an inboard motor. Meanwhile, the study aims to obtain an optimal interaction between the propulsion system and the hull shape of the ship. It was conducted by calculating the ship’s resistance using the van Oortmerssen method, and validating the result using the CFD method. Furthermore, thrust and torque calculations were performed to obtain the characteristics of the ship’s propellers, and the results were validated using the CFD method. The result obtained from the calculation of the ship’s resistance was a New Fishing Vessel engine power of 11 HP. 4 types of B-Series propellers characterized based on the size of their pitch, including 14.00 inch, 14.25 inch, 14.50 inch, and 14.75 inch were, analyzed using the engine propeller matching analysis. The results show that the propeller with the pitch size of 14.75 inches was the best, as it had a power of 100%, speed of 25.35%, and efficiency of 32%. Therefore, it was chosen as the new propeller for New Fishing Vessels.
Keywords: resistance, thrust, torque, engine propeller matching, CFD